Exploring public awareness and spreading pattern analysis of COVID-19 outbreak in Bangladesh - Hossain, Md Jamal; Ahmmed, Foyez; Kuddus, Md Ruhul; Alam, Safaet; Rahman, SM Abdur (Bangladesh Journal of Medical Science, 2021)
Background: The highly transmissible coronavirus disease 2019 (COVID-19) has plagued the worldwide population with a continuous upward thrust of the death toll, which might be related to insufficient knowledge, attitudes, and behavioral (KAB) score, and public awareness. Objective: The current research sought to explore public awareness in terms of knowledge, attitudes, and behavioral responses toward COVID-19 and analyze its spreading pattern during the embryonic phase in Bangladesh. Methods: From March 19 to April 15 of 2020, seventeen planned questions were answered by the Bangladeshi respondents recruited through a simple snowball sampling technique. Informed consent from each participant was taken in the survey. Results: Out of the total participants (n = 1861), 34.65% were female, and 40.83% had an education level up to Junior School Certificate (JSC). Among all the demographic variables, the highest average knowledge, attitudes and behaviors scores (mean ± SD) were reported for 18- 30 years age group (4.07 ± 1.01 out of 5; 95% confidence interval, [CI] = 4.01-4.13; p< 0.001), above 50 years age group (1.70 ± 0.64 out of 3; 95% CI = 1.59-1.80; p< 0.001), and bachelor or higher degree group (2.64 ± 0.83 out of 4; 95% CI = 2.57-2.70, p< 0.001), respectively. It was clearly depicted that the obtained knowledge score was associated with poor attitudes and behaviors. Conclusion: Education on basic health sciences as well as overwhelming campaign and publicity must be pointed at enhancing KAB scores towards COVID-19 in Bangladesh. Bangladesh Journal of Medical Science Vol.20(5) 2021 p.108-117